Pioneer migrants in the land of promise - Dacudao, Patricia Irene (Philippine Population Review, 2010)
This paper looks at how migrants came to Davao in the first half of the last century. Of the major cities in the Philippines today, Davao has a unique history of having been settled by a relatively large number of foreigners, particularly Americans and Japanese, hand-in-hand with Filipino settlers. This paper aims to answer the question why these diverse peoples went to a politically and geographically peripheral place, and what travails they encountered in that frontier situation. For the Filipino settlers, the push and pull factors of migration will be explored. This paper traces their particular places of origin using the Philippine Census and the San Pedro Parish Records, and finds answers to the question why such large numbers left their hometowns to go to Davao (the push factor). For the pull factor, worker benefits and the burgeoning plantation economy will be studied as to its influence in enticing thousands of Filipinos from the Visayas to migrate to the Davao frontier.